2016
DOI: 10.1017/s0960258516000106
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of short-term germination delay on fitness of the annual weed Agrostemma githago (L.)

Abstract: Time of seedling emergence is an important step in the life cycle of annual plants because it may determine subsequent performance and success. Timing of emergence is especially critical to plant performance in habitats like arable fields which are subject to frequent disturbances. Within-season variation in timing of germination in the range of only a few days is typical for many arable weeds. However, since it is unclear whether such small deviations in germination date translate into fitness differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
0
13
1
Order By: Relevance
“…We found that the commonly used anthelmintic Cydectin (0.1% moxidectin) can reduce seedling number by almost two thirds and lead to a 12-d delay of germination when applied in a 10 mg l -1 concentration. Already a 7-d delay of germination can lead to significantly reduced plant fitness in terms of biomass and flower production as has been shown for the arable weed species Agrostemma githago [37]. In contrast to our results, an authorisation study that tested the germination response of 12 herbaceous plant species to moxidectin did not find adverse effects [11].…”
Section: Discussioncontrasting
confidence: 78%
“…We found that the commonly used anthelmintic Cydectin (0.1% moxidectin) can reduce seedling number by almost two thirds and lead to a 12-d delay of germination when applied in a 10 mg l -1 concentration. Already a 7-d delay of germination can lead to significantly reduced plant fitness in terms of biomass and flower production as has been shown for the arable weed species Agrostemma githago [37]. In contrast to our results, an authorisation study that tested the germination response of 12 herbaceous plant species to moxidectin did not find adverse effects [11].…”
Section: Discussioncontrasting
confidence: 78%
“…The point of germination initiation as well as habitat characteristics is crucial for seedling fate. In highly competitive and stable environments, where struggle for light predominates, early emergence is beneficial for plant fitness (Orrock & Christopher 2010;Rühl et al 2016). By contrast, in ecosystems characterized by drought periods, accelerated emergence bears the risk of higher seedling mortality due to sudden water limitations (Orrock & Christopher 2010;Ludewig et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…higher MGT, poses the risk that seedling development does not correspond to climate patterns species are adapted to [ 65 ]. Later germination in spring reduces biomass development above- and belowground compared to older seedlings [ 66 ]. These effects may be so strong that seedlings germinating later in spring can not develop sufficient root-soil contact to endure subsequent warmer and dryer summer periods and therefore may have a lower survival probability.…”
Section: Discussionmentioning
confidence: 99%